Potential Probiotic Pediococcus pentosaceus M41 Modulates Its Proteome Differentially for Tolerances Against Heat, Cold, Acid, and Bile Stresses - Baig, Mohd Affan; Turner, Mark S.; Liu, Shao-Quan; Al-Nabulsi, Anas A.; Shah, Nagendra P.; Ayyash, Mutamed M. (Frontiers in Microbiology, 2021)
Probiotics containing functional food confer health benefits in addition to their nutritional properties. In this study, we have evaluated the differential proteomic responses of a potential novel probiotic Pediococcus pentosaceus M41 under heat, cold, acid, and bile stress conditions. We identified stress response proteins that could provide tolerances against these stresses and could be used as probiotic markers for evaluating stress tolerance. P. pentosaceus M41 was exposed to 50 oC for 2h (heat stress), 4 oC for 2h (cold stress), pH 3.0 for 2 h (acid stress), and 0.05% bile for 2h (bile stress). Proteomic analysis was carried out using 2D-IEF SDS PAGE and LC-MS/MS. Out of 60 identified proteins, 14 upregulated and 6 downregulated proteins were common among all the stress conditions. These proteins were involved in different biological functions such as translation-related proteins, carbohydrate metabolism (phosphoenolpyruvate phosphotransferase), histidine biosynthesis (imidazole glycerol phosphate synthase), and cell wall synthesis (tyrosine-protein kinase CapB). Proteins such as polysaccharide deacetylase, lactate oxidase, transcription repressor NrdR, dihydroxyacetone kinase were upregulated under three out of the four stress conditions. The differential expression of these proteins might be responsible for the tolerance and protection of P. pentosaceus M41 against different stress conditions.